2012
DOI: 10.1007/s10706-012-9504-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying on the Index Properties of Lateritic Soils

Abstract: Due to significant variation in geological and climatic conditions the characteristics of lateritic soils vary from place to place. Because of the prevailing climatic conditions, the laterites and lateritic soils of a particular region may be different from those found in other parts of the world. Some investigators report that the pretest drying has significant effect on the properties of soils. In such studies the authors associate the effect of drying on the properties of soils due to the mineralogy of soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…The bulk sample was sieved by straining with a rubber spatula to prepare slurries with particles < 425 μm, which is equivalent to the size fraction for soil mechanical testing. As the material properties of soil vary with heating and drying (e.g., Terzaghi et al 1996;Sunil and Krishnappa 2012;Huvaj and Uyeturk 2018), two types of slurry were examined: one prepared from soil dried at 40 ℃ in an oven (water content of 5.2 wt%), and another made using moist soil that was not allowed to dry between sampling and slurry Kameda et al 2019). Weathered tephra samples were collected from the clay layer in the Ta-d layer that is in contact with the underlying Neogene sedimentary rock.…”
Section: Samplesmentioning
confidence: 99%
“…The bulk sample was sieved by straining with a rubber spatula to prepare slurries with particles < 425 μm, which is equivalent to the size fraction for soil mechanical testing. As the material properties of soil vary with heating and drying (e.g., Terzaghi et al 1996;Sunil and Krishnappa 2012;Huvaj and Uyeturk 2018), two types of slurry were examined: one prepared from soil dried at 40 ℃ in an oven (water content of 5.2 wt%), and another made using moist soil that was not allowed to dry between sampling and slurry Kameda et al 2019). Weathered tephra samples were collected from the clay layer in the Ta-d layer that is in contact with the underlying Neogene sedimentary rock.…”
Section: Samplesmentioning
confidence: 99%
“…Compared with lateritic soil tested at NMC, the SG of the three genetically different lateritic soils were lower and decreased as the drying temperature increases from air to oven drying at 110 • C. The difference is, however, not significant. Sunil and Krishnappa [22] studied "the influence of drying on the properties of lateritic soils and observed that the SG of the air and oven dried lateritic soils did not vary significantly from each other. At NMC and all the pretest drying temperatures, the average SG of charnockite-derived lateritic soil is higher compared to the other lateritic soils.…”
Section: Resultsmentioning
confidence: 99%
“…These investigations show that a higher drying temperature leads to an accumulation of fine particles with organic and to larger grains with decreasing specific surface area (Mikutta et al 2005). There is also an irreversible dehydration process of the clay particles causing cementation of fine particles which are then not dispersed (Sunil, Krishnappa 2012). These effects can even be detected in a standard grainsize analysis.…”
Section: Disintegration Test After Endellmentioning
confidence: 93%
“…Some of the samples needed to be dried, which seems to have a considerable influence on the aggregate stability, particularly for the fine-grained, organic materials. The influence of the drying temperature in soil sample preparation on the aggregation has already been investigated by different researchers (Basma et al 1994;Sunil, Krishnappa 2012). These investigations show that a higher drying temperature leads to an accumulation of fine particles with organic and to larger grains with decreasing specific surface area (Mikutta et al 2005).…”
Section: Disintegration Test After Endellmentioning
confidence: 98%